Assessment of electrode-based spontaneous eye blink analysis - (:unkn) unknown (My University, 2011)
In this paper, we assess the use of electrode based spontaneous eye blink recording technique (which is considered to be a suitable indicator for fatigue diagnostics) through experiments, and conclude that the electrode based measurement of eye blink parameters has some drawbacks as compared to optical methods.
Keywords: Digital filters; Electrodes; Eye blink; Prevention of occupational accidents